2004
DOI: 10.1063/1.1664034
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring the Er–Yb distribution to improve the photoluminescence response of thin films

Abstract: Thin films of amorphous aluminum oxide (a-Al2O3) codoped with Er3+ and Yb3+ ions have been in-depth nanostructured by distributing the rate earth (RE) ions in layers separated in the 0–3 nm range. The Yb to Er concentration ratio is varied from 0 to 3.6. The photoluminescence (PL) response at 1.53 μm exhibits an increase of up to two orders of magnitude with respect to that of films doped only with Er. The PL intensity is improved when Yb3+ and Er3+ ions are in separate layers and the results show that efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…8 A glass host with maximum phonon energy of 880 cm −1 , corresponding to the exchange of five phonons, is expected to be suited for high luminescence quantum efficiency. 4,6,8 In the case of amorphous Al 2 O 3 a phonon energy spectrum has been reported with maximum phonon energy value of 870 cm −1 , 10 which is consistent with the clear observation of the 1480 nm emission in Fig. 2.…”
Section: +supporting
confidence: 74%
See 1 more Smart Citation
“…8 A glass host with maximum phonon energy of 880 cm −1 , corresponding to the exchange of five phonons, is expected to be suited for high luminescence quantum efficiency. 4,6,8 In the case of amorphous Al 2 O 3 a phonon energy spectrum has been reported with maximum phonon energy value of 870 cm −1 , 10 which is consistent with the clear observation of the 1480 nm emission in Fig. 2.…”
Section: +supporting
confidence: 74%
“…9 In our previous works we have shown that alternate pulsed laser deposition ͑PLD͒ from the host ͑Al 2 O 3 ͒ and dopant rare earth ͑RE͒ targets can be used to obtain artificial structures in which the RE concentration and ion distribution are controlled. 10,11 An ArF excimer laser ͓ = 193 nm, = 20 ns full width at half maximum ͑FWHM͒, 2 J cm −2 ͔ was used to ablate independently the Al 2 O 3 and RE targets. The films were designed to have a 300 nm total thickness.…”
mentioning
confidence: 99%
“…However, the Er profile and separation can be controlled by using alternating targets. This has been investigated for Er-doped and Er-, Yb-co-doped alumina thin films using PLD [185][186][187][188]. One of the advantages of this technique is that the Er concentration can be tailored such that it is highest where the pump light intensity is highest, thus potentially improving the pumping efficiency.…”
Section: Waveguide Fabrication Methodsmentioning
confidence: 99%
“…Extensive researches proved that Al 2 O 3 can enhance dispersion of Er 3+ , increasing luminescence efficiency and decay time, moreover, it has high chemical durability, thermal stability, and mechanical strength [6,7] . The Er 3+ doped Al 2 O 3 material has been successfully prepared by chemical vapor deposition [8] , ion implantation [9] , laser ablation deposition [10] , sol-gel method [11] , etc.…”
mentioning
confidence: 99%